Proceedings of the Ocean Drilling Program 1993
DOI: 10.2973/odp.proc.sr.130.033.1993
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetic Analyses of Short Normal Polarity Magnetic Anomalies in the Matuyama Chron

Abstract: We document three short normal intervals in the natural remanent magnetization of sediments within the Matuyama Chron. These three anomalous zones of magnetization between the Jaramillo and Olduvai subchrons were identified from continuous measurements of archive halves from Hole 803 A using the pass-through 2G cryogenic magnetometer at Scripps. The U-channel samples were taken from the three intervals, analyzed using the pass-through system, and then cut into discrete 1 -cm-thick samples. Measurements on disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…by a succession of at least two geomagnetic events (M3 and M4). This is supported by the available paleointensity data, which show three periods of low field intensity associated with the Ontong Java 1 and 2 and the Gilsa events [Gallet et al, 1993;Valet and Meynadier, 1993] (see also for the youngest Ontong Java event). To date, larg• changes in geomagnetic direction have only been found for the event slightly younger than the Olduvai subchron, identified as Gilsa by Liddicoat et at [1980] and Clement and Kent [1987]; however, the excursional nature of the geomagnetic field also seems very probable for the two other events.…”
Section: The Comparison Between the Near-bottom Results And The Paleosupporting
confidence: 65%
See 1 more Smart Citation
“…by a succession of at least two geomagnetic events (M3 and M4). This is supported by the available paleointensity data, which show three periods of low field intensity associated with the Ontong Java 1 and 2 and the Gilsa events [Gallet et al, 1993;Valet and Meynadier, 1993] (see also for the youngest Ontong Java event). To date, larg• changes in geomagnetic direction have only been found for the event slightly younger than the Olduvai subchron, identified as Gilsa by Liddicoat et at [1980] and Clement and Kent [1987]; however, the excursional nature of the geomagnetic field also seems very probable for the two other events.…”
Section: The Comparison Between the Near-bottom Results And The Paleosupporting
confidence: 65%
“…However, magnetostratigraphic results obtained from deep-sea sediments indicate that the duration of the Cobb Mountain event is likely longer, perhaps -25,000 years [Clement and Kent, 1987;Gallet et al, 1993]. The paleointensity data obtained by several authors [e.g., Valet and Meynadier, 1993;Kok and Tauxe, 1999] all show a period of low field intensity around 1.2 Ma, with some evidence for a field recovery during the middle of this interval [Gallet et al, 1993]. The two synthetic profiles exhibit a pronounced anomaly associated with the Cobb Mountain event.…”
Section: Matuyama Chron In the Deep-tow Stacked Profile The Matuyamamentioning
confidence: 96%
“…Two other short low intensity intervals have also been recently documented by Gallet et al (1993), who studied the record from Hole 803A in the Ontong Java Plateau (Leg 130). These last two intervals were named Ontong Java 1 and Ontong Java 2 (Gallet et al, 1993). Champion et al (1988) noticed that the timing of these events appears to be more or less regular.…”
Section: Excursions and Short Polarity Eventsmentioning
confidence: 74%
“…Thermal experiments were used to obtain relative paleointensities of the geomagnetic field. Earlier work on one of the cores showed that thermal demagnetization techniques were able to identify some anomalous zones in the reversed Matuyama Chron as low intensity instead of normal-polarity intervals [Gallet et al, 1993].…”
Section: Discussionmentioning
confidence: 99%
“…A shore-based paleomagnetic study [Gallet et al, 1993] documented the magnetic characteristics of the sediments from Site 130-803 used here. Hysteresis parameters and isothermal remanent magnetization acquisition data indicated either a magnetic carrier in the pseudo-single-domain range or a rather uniform mixture of grain sizes of magnetite.…”
Section: Previous Work On Leg 130 Sedimentsmentioning
confidence: 99%